5 + 4 - 7 = 4x + 3 - x
9 - 7 = 3x + 3
2 = 3x + 3
2 - 3 = 3x + 3 - 3
-1 = 3x
-1/3 = 3x/3
-1/3 = x
2006-11-07 11:38:25
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
start with the left side, 5+4=9 and 9-7=2, so we know 2=4x+3-x
Next we combine like terms, 4x and x. subtract the x from 4x and you get 3x. so we know that 2=3x+3. Now we have to use inverse operations to get rid of +3. The opposite of adding is subtracting, so subtract 3 from both sides of the equation.
You should get -1=3x. once again we must use inverse operations to get x by itself. The opposite of multiplication is division, so we are going to divide by 3 on both sides. your final answer should b -1/3=x
2006-11-07 18:32:38
·
answer #2
·
answered by sj 3
·
1⤊
0⤋
5 + 4 - 7 = 3x + 3
2 = 3x + 3
-1 = 3x
-1/3 = x
So -1/3 is the answer for x
2006-11-07 18:29:17
·
answer #3
·
answered by poker5495 4
·
0⤊
0⤋
5+4-7=4x+3-x
9-7=4x+3-x
2=4x+3-x
-1=4x-x
-1=3x
-1/3=x
just get the constants on one side and the variables on the other and add/subtract. hopefully i didnt make a stupid mistake somewhere in there ;) but you get the general idea.
2006-11-07 18:30:18
·
answer #4
·
answered by nemahknatut88 2
·
1⤊
0⤋
5 + 4 - 7 = 4x + 3 -x
2=3x+3
3x=-1
x=-1/3
2006-11-07 18:34:20
·
answer #5
·
answered by yupchagee 7
·
1⤊
0⤋
5 + 4 - 7 = 4x + 3 - x
9 - 7 = 3x + 3
2 = 3x + 3
2 - 3 = 3x + 3 - 3
- 1 = 3x
- 1/3 = 3x/3
- 1/3 = x
The answer is x = - 1/3
- - - - - - - -s-
2006-11-07 18:35:51
·
answer #6
·
answered by SAMUEL D 7
·
1⤊
0⤋
5+4=9
9-7=4x+3-x
2=4x+3-x
-subtract 3 from 2
2-3= -1
4x-x=3x
-divide 3x by -1
x= -1/3
i think thats how you do it
2006-11-07 18:31:30
·
answer #7
·
answered by princesschristine91 1
·
1⤊
0⤋
The answer is 3/2
2006-11-07 18:31:12
·
answer #8
·
answered by Taylor R 2
·
0⤊
2⤋
2 = 3x+3 (just simplified)
-1 = 3x
x= -1/3
2006-11-07 18:30:02
·
answer #9
·
answered by Anonymous
·
1⤊
0⤋
x=32
2006-11-07 18:28:55
·
answer #10
·
answered by DAWN M 1
·
0⤊
2⤋